2007
DOI: 10.1174/021037007782334346
|View full text |Cite
|
Sign up to set email alerts
|

Una intervención educativa integrada sobre las habilidades argumentativas escritas en estudiantes de 4° de la E.S.O.

Abstract: Publication details, including instructions for authors and subscription information: http://www.tandfonline.com/loi/riya20Una intervención educativa integrada sobre las habilidades argumentativas escritas en estudiantes de 4° de la E.S.O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…In some studies complementary help was also offered to the student, when working individually or with peers, through external supports such as writing guides (Castelló & Monereo, 1996; Gárate, Melero, Tejerina, Echevarría, & Gutiérrez, 2007) or what Del Longo and Cisotto (2014) named writing tools. This helped the students to progressively assume control of the task in the absence of the teacher’s guidance.…”
Section: Previous Studies On Intervention Proposalsmentioning
confidence: 99%
“…In some studies complementary help was also offered to the student, when working individually or with peers, through external supports such as writing guides (Castelló & Monereo, 1996; Gárate, Melero, Tejerina, Echevarría, & Gutiérrez, 2007) or what Del Longo and Cisotto (2014) named writing tools. This helped the students to progressively assume control of the task in the absence of the teacher’s guidance.…”
Section: Previous Studies On Intervention Proposalsmentioning
confidence: 99%
“…Intervention studies on self-regulation strategies with primary students have showed that students significantly improved their writing skills (e.g., Fidalgo et al, 2009;Fidalgo et al, 2011;Ripoll Salceda et al, 2013;Salas et al, 2020). Other studies centered on the effectiveness of instructional programs and techniques in different instructional programs to teach writing to secondary school students (e.g., Casado-Ledesma et al, 2021;Gárate et al, 2014). Qualitative studies have focused on the implementation of specific teaching strategies, particularly teaching units that integrate project work and metalinguistic awareness activities (for a review, see Camps & Fontich, 2020;Reig, 2020;Ribas Seix et al, 2020;Santolària Orrios, 2021).…”
Section: The Teaching Of Writing and Evidence-based Writing Practicesmentioning
confidence: 99%
“…A primary focus of cognitive task research is how instruction in reading of argumentative texts transfers to writing those texts (Bergmann & Zepernick, 2007;Wardle, 2007). Researchers have examined the relationship between students' reading ability in interpreting and writing texts (Gárate, Melero, Tejerina, Echevarría, & Gutiérrez, 2007;Parodi, 2007;Sadoski & Paivio, 2001), as well as how writing argumentative texts transfers back to reading those texts (Wiley & Voss, 1999). In a large-scale study, eighth graders were assigned to write an essay based on a specific purpose, text type, topic, audience, and register, as well as to answer nine openended questions in response to argumentative texts (Parodi, 2007).…”
Section: Integrating Reading and Writing Argument Instructionmentioning
confidence: 99%